2014
DOI: 10.1038/ncomms6519
|View full text |Cite
|
Sign up to set email alerts
|

Control of cotton fibre elongation by a homeodomain transcription factor GhHOX3

Abstract: Cotton fibres are unusually long, single-celled epidermal seed trichomes and a model for plant cell growth, but little is known about the regulation of fibre cell elongation. Here we report that a homeodomain-leucine zipper (HD-ZIP) transcription factor, GhHOX3, controls cotton fibre elongation. GhHOX3 genes are localized to the 12th homoeologous chromosome set of allotetraploid cotton cultivars, associated with quantitative trait loci (QTLs) for fibre length. Silencing of GhHOX3 greatly reduces (>80%) fibre l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
228
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(234 citation statements)
references
References 49 publications
6
228
0
Order By: Relevance
“…Recently, significant progress has been made in large-scale identification of genes and proteins involved in fiber development, particularly of those related to fiber elongation and secondary wall deposition (Arpat et al, 2004;Cao, 2015;Gou et al, 2007;Jin et al, 2013;Shi et al, 2006;Zhao et al, 2010). Moreover, a number of fiber development-related genes have been structurally or functionally characterized (Han et al, 2013;Li et al, 2005;Pei, 2015;Ruan et al, 2003;Shan et al, 2014;Xu et al, 2013;Zhang et al, 2011). These studies have made important progress towards understanding the molecular mechanisms governing cotton fiber development.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant progress has been made in large-scale identification of genes and proteins involved in fiber development, particularly of those related to fiber elongation and secondary wall deposition (Arpat et al, 2004;Cao, 2015;Gou et al, 2007;Jin et al, 2013;Shi et al, 2006;Zhao et al, 2010). Moreover, a number of fiber development-related genes have been structurally or functionally characterized (Han et al, 2013;Li et al, 2005;Pei, 2015;Ruan et al, 2003;Shan et al, 2014;Xu et al, 2013;Zhang et al, 2011). These studies have made important progress towards understanding the molecular mechanisms governing cotton fiber development.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber length is a key factor determining cotton quality with the yield of cotton fiber depends mainly on the number of fiber cells of each ovule. Phytohormones, including ethylene and gibberellins (GA), are proposed to regulate cotton fiber initiation and elongation [4,5]. Comparative genomics analysis revealed that neither extremely high level of ethylene in D genome nor low level in A genome is beneficial to cotton fiber development, which suggest that fine-tuning of ethylene biosynthesis is necessary for normal cotton fiber cell elongation and maturation.…”
mentioning
confidence: 99%
“…This research uncovers the molecular mechanism of GA Figure 1 (color online) A model for regulation of cotton fiber elongation by GhHOX3 and the phytohormone GA [1]. A, In cotton fibers, DELLA proteins bind to HOX3 to prevent its binding to other HD-ZIP transcription factors, repressing their transcriptional activation to target genes.…”
mentioning
confidence: 99%
“…Recently, Chen and colleagues from Shanghai Institute of Plant Physiology and Ecology of Chinese Academy of Sciences, in collaboration with scientists from Nanjing Agricultural University and from the US, have identified a homeodomain (HOX)-containing transcription factor that plays a central role in controlling cotton fiber elongation [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation